CLINICAL-EPIDEMIOLOGICAL CHARACTERIZATION OF GUILLAIN BARRÉ SYNDROME IN A CUBAN CASE SERIE. - Lestayo O’Farrill, Zurina; Sistach-Vega, Vivian; Rodriguez Álvarez , Bismary; Hoya González, Adarilis; González-Quevedo, Alina; Gutiérrez-Gil, Joel; Persaud, Alex; Hernández-Cáceres, José Luis; González, Ricardo (RRNMF Neuromuscular Journal, 2021)
Background: The broad spectrum of Guillain Barré Syndrome (GBS) includes different pathological phenotypes, with a heterogeneous distribution. The reports, by country and region, have shown its great variability and clarified its behavior. Objective: Characterize GBS and define the most frequent phenotypes. Methods: A time series was constructed to analyze the epidemiological behavior of GBS. The demographic, epidemiological, clinical and complementary aspects of 167 patients were retrospectively described. The severity was analyzed and the patients were classified. Results: The mean age was 33 years, 22.8% were children. The incidence decreased with age and a seasonal preference was seen for the month of August, that usually coincides with higher rates of respiratory and digestive infections. Dengue preceded some GBS outbreaks. The Acute Inflammatory Demyelinating Polyradiculopathy (AIDP) variant predominated and was most severe. Regional variants, a recurrent GBS and a family one were detected. Age, personal history of autoimmune disease, preceding infectious phenomenon, latency between the preceding phenomenon and the onset of the clinical picture, the extent of the motor disorder, facial involvement, gait impairment, ventilatory compromise, and degradation of the osteotendinous reflexes, significantly correlated with the severity. Conclusions: The predominance of AIDP coincides with some countries in the area, with varying geographical location and climatic conditions. The incidence decreases with age. The relationship between the severity and the personal history of autoimmune disease, the preceding infectious phenomenon, and the latency between the preceding phenomenon and the onset of the clinical picture, could be reflecting an underlying autoimmune mechanism in each case.